A Performance Evaluation Method of Power Distribution and Utilization Communication Network Based on Improved TOPSIS - Lingli Meng; Ningning Chen; Jiang Wang; Peng Yu (Dianxin kexue)
Aiming at problems of AHP, the weight determining methods of the multi-index comprehensive evaluation system was studied, and a performance evaluation method of power distribution and utilization communication network based on the improved TOPSIS was proposed. The method puts forward that combine SAW, TOPSIS with the improved AHP to evaluate the performance of the power distribution and utilization communication network. As the basic TOPSIS method cannot process the data on the perpendicular bisector, the TOPSIS method based on the relative entropy was proposed. The simulation results show that the improved TOPSIS method is more suitable for evaluating the sensitive indicators of electric communication network.